Tranexamic Acid in Total Knee Arthroplasty: A Comprehensive Examination of Double-Dose Strategies for Hemostasis - Kazez, Muhammed; Yalın, Mustafa; Key, Sefa (Kafkas Üniversitesi, 2025)
Aim: The current study aimed to evaluate the impact of administering tranexamic acid (TXA) through intravenous (IV) or intraarticular (IA) routes, in double doses, in conjunction with postoperative drain clamping (DC), on postoperative bleeding, transfusion requirements, and thromboembolic complications in patients undergoing total knee arthroplasty (TKA). Material and Methods: A retrospective review of 96 patients undergoing unilateral primary TKA for gonarthrosis between 2021 and 2022 was conducted. Patients received either double-dose IV TXA (n=52), double-dose IA TXA (n=26), or no TXA (n=18) along with postoperative DC. Various parameters were compared among groups, including preoperative and postoperative hemoglobin (Hb) levels, blood transfusion requirements, and length of hospital stay (LOS). Results: Both IV and IA double-dose TXA significantly reduced postoperative bleeding compared to no TXA administration. The need for blood transfusion was lowest in the double-dose IV TXA group. No significant differences were observed in thromboembolic complications among the groups. Length of hospital stay (LOS) was significantly shorter in the TXA groups compared to the no TXA group. Conclusions: Administration of double-dose TXA, either IV or IA and postoperative DC effectively reduced postoperative bleeding in TKA patients. Double-dose IV TXA demonstrated the lowest transfusion rates, suggesting a potential advantage in reducing transfusion requirements. Both IV and IA TXA administrations were safe and efficacious, with no significant increase in thromboembolic complications, emphasizing their overall safety profile in TKA patients.
Keywords: Orthopaedics; Ortopedi